Characteristics and reducibility of nanosized La1-xCexCoO3 perovskites synthesized by reactive grinding - Thao, Nguyen Tien; Thuan, Ngo Thi (Vietnam Journal of Chemistry, 2014)
Two (La,Ce)CoO3 perovskite-type oxides prepared by reactive grinding have been characterized by means of X-ray diffraction, N2 adsorption/desorption isotherms, SEM, H2-TPR. Both samples show a nanocrystalline phase and rather high surface area. The thermal stability of cobalt ions in such solids has been studied under reducing conditions. H2-TPR results indicate that the reduction of Co3+ to Co0 occurs in a multiple-step. The partial replacement of La3+ by Ce4+ has promoting effects on the reducibility of cobalt ions. A decreased reduction temperature of cobalt ions in the presence of Ce4+ leads to an increased dispersion of the reduced phase for La0.9Ce0.1CoO3 perovskite precursor. Keywords: perovskite; reduction; cobalt; La-Ce-Co; dispersion; metal.